New Horizons of Forest Planning and Financing - Seth, V. K.; Sudhakara Rao, Y. (Indian Forester, 1970)
In spite of the sizeable forest area of India, its contribution to the national economy is not appreciable (being 7%). Projections of wood requirements show that by 1980 the demand for industrial wood will be 27 million cubic metres as against the present production figure of 7 million cubic metres. The challenge before the Forester would be to supply the spiralling needs of a developing industrial economy. This can be met by regarding forestry as an economic activity and investing heavily on measures to maximize production. Forestry improvement works are a long-term investment, requiring continuity of plan. Several instances have been given in this paper of the setting up of autonomous bodies and national forestry funds in different countries. The scope of participation by bodies like the Agriculture Refinance Corporation, Life Insurance Corporation, Industrial Finance Corporation, banks and industries has been highlighted.